WORK PERFORMED THROUGHOUT THE LIFE OF RETIREES AND FACTORS ASSOCIATED WITH PHYSICAL INACTIVITY AND HEALTH CONDITIONS - Pollyanna Natalia Micali; Jamile Sanches Codogno (Journal of Physical Education)
ABSTRACT This study aimed to identify the most prevalent chronic diseases among retired residents in the city of Rio Claro-SP and possible associations of work performed during their lives (manual or intellectual) with physical inactivity, body mass index, diseases, and expenses with health services. This is a cross-sectional population study with retired individuals, performed at two moments (2014 and 2018). Instruments used for data collection: Survey of Referred Morbidities; Questionnaire developed by Pimenta (2006); International Physical Activity Questionnaire; Body mass index The statistical tests applied were the Chi-square test, by Kruskal-Wallis and Mann Whitney with the Bonferroni adjustment. The sample of the present study was composed of 171 retirees, with the highest prevalence of married individuals (81.3%), with secondary education incomplete (53.8%), economic class "C" (49.1%), manual work performed throughout life (54.4%), obese (49.1%), and sedentary (33.9%). The association analysis demonstrated that the majority of the sample who performed manual work throughout life was associated with hypertension (p= 0.01) and Osteoarthritis (p 0.01). It is concluded that manual labor seems to present a greater risk for the development of chronic diseases.